Kazakhstan development finance assessment.
Meeting the 2030 Agenda for Sustainable Development requires unprecedented investment from different sources. In recent years, total available development finance in Kazakhstan stagnated and decreased significantly as a share of gross domestic product. The publication also includes a review of existing policies and partnerships along with recommendations that are aligned with achieving the Sustainable Development Goals.